Health promotion in mental health care: perceptions from patients and mental health nurses. Issue 11 (7th January 2013) - Verhaeghe, Nick; De, Jan; Maes, Lea; Van, Cornelis; Annemans, Lieven
<x xml:space="preserve">Abstract</x> Aims and objectives To gain insight into the factors influencing the integration of physical activity and healthy eating into the daily care of individuals with mental disorders (MD) living in sheltered housing and to increase the understanding of the relationships between and complexities of these factors. Background Growing attention is given to the implementation of health promotion activities in mental health care. By improving the understanding of perceptions of patients and mental health nurses, health promotion programmes targeting physical activity and healthy eating can be developed that better meet the patients' needs. Design A descriptive qualitative study. Methods Based on a purposive sampling strategy, three focus groups including 17 mental health nurses and individual interviews with 15 patients were conducted. Results Although physical and mental health benefits of physical activity and healthy eating were identified, several barriers to integrate healthy lifestyles into the daily life of patients were reported. Important barriers identified by the patients consisted of lack of energy and motivation as a result of the MD, side effects of psychotropic drug use, and hospitalisation. Lack of time and personal views and attitudes towards health promotion were reported by the mental health nurses as important elements influencing the way in which they integrate health promotion in the care provided. Support from the mental health nurse was considered important by the patients in changing their unhealthy lifestyle behaviour. Conclusions The results of the study provide insight into important factors influencing the integration of health promotion activities targeting physical activity and healthy eating in individuals with MD living in sheltered housing. Relevance to clinical practice The information derived from this study is useful and relevant in the design and implementation of health promotion interventions targeting physical activity and healthy eating in people with MD living in sheltered housing.